Improving awareness, understanding, and enforcement of responsibilities and regulations in Blue Biotechnology - Schneider, Xenia T.; Stroil, Belma K.; Tourapi, Christiana; Rebours, Céline; Novoveská, Lucie; Vasquez Christodoulou, Marlen; Gaudêncio, Susana P. (My University, 2023)
Blue Biotechnology is developing rapidly worldwide. However, the Nagoya Protocol (NP), Responsible Research and Innovation (RRI) and other regulatory requirements in this field are falling behind. This article identifies the main RRI, NP, and regulatory gaps and provides key recommendations to mitigate these challenges.
Keywords: Areas Beyond National Jurisdiction; Biodiversity Beyond National Jurisdiction; Blue Biotechnology; Nagoya Protocol; responsible research and innovation; Second World Ocean Assessment